The synergy of BET inhibitors with aurora A kinase inhibitors in MYCN-amplified neuroblastoma is heightened with functional TP53 - Yi, Joanna S. (Neoplasia, 2021)
Amplification of MYCN is a poor prognostic feature in neuroblastoma (NBL) indicating aggressive disease. We and others have shown BET bromodomain inhibitors (BETi) target MYCN indirectly by downregulating its transcription. Here we sought to identify agents that synergize with BETi and to identify biomarkers of resistance. We previously performed a viability screen of ∼1,900 oncology-focused compounds combined with BET bromodomain inhibitors against MYCN-amplified NBL cell lines. Reanalysis of our screening results prominently identified inhibitors of aurora kinase A (AURKAi) to be highly synergistic with BETi. We confirmed the anti-proliferative effects of several BETi+AURKAi combinations in MYCN-amplified NBL cell lines. Compared to single agents, these combinations cooperated to decrease levels of N-myc. We treated both TP53-wild type and mutant, MYCN-amplified cell lines with the BETi JQ1 and the AURKAi Alisertib. The combination had improved efficacy in the TP53-WT context, notably driving apoptosis in both genetic backgrounds. JQ1+Alisertib combination treatment of a MYCN-amplified, TP53-null or TP53-restored genetically engineered mouse model of NBL prolonged survival better than either single agent. This was most profound with TP53 restored, with marked tumor shrinkage and apoptosis induction in response to combination JQ1+Alisertib. BETi+AURKAi in MYCN-amplified NBL, particularly in the context of functional TP53, provided anti-tumor benefits in preclinical models. This combination should be studied more closely in a pediatric clinical trial.